Mucocele of the appendix: appendectomy or colectomy? - Abreu Filho,Janduí Gomes De (2011)
Mucocele of the appendix is a rare disease. It can be triggered by benign or malignant diseases, which cause the obstruction of the appendix and the consequent accumulation of mucus secretion. The preoperative diagnosis is difficult due to non-specific clinical manifestations of the disease. Imaging tests can suggest the diagnosis. The treatment is always surgical and depends on the integrity and size of the appendix base and on the histological type of the original lesion. The prognosis is good in cases of integrity of the appendix. The perforation of the appendix and subsequent extravasation of its contents into the abdominal cavity may lead to pseudomyxoma peritonei, which has very poor prognosis if not treated properly.